ANALYSIS THE IMPACT OF PRODUCT QUALITY AND CUSTOMER SERVICE ON SATISFACTION AND LOYALTY OF PEST CONTROL OPERATORS IN PT BAYER INDONESIA - Sugiarman Sugiarman; Rita Nurmalina; Kirbrandoko Kirbrandoko (Pusbindiklat - LIPI, 2015)
The aims of the research are to identify the important level of attributes of product quality and customer service on customer satisfaction and loyalty, to analyze the impact of product quality and customer service oncustomer satisfaction and loyalty, and to recommend the corporate strategy to PT Bayer Indonesia on customer satisfaction and loyalty. Types of research are descriptive and explanatory survey and the sampling method is convenientsampling. Unit of observation is two hundreds respon dents through the distribution of questionnaires to the pest control operators in Jakarta, Bandung, Semarang, Surabaya, Denpasar, Balikpapan, Medan, and Pekanbaru.Attributes and its influence was analyzed using Structural Equation Model (SEM). Respondents of the study are from Jakarta (46.0%), Bandung (2.5%), Semarang (3.0%), Surabaya (25.0%), Denpasar (5.5%), Balikpapan (2.5%), Pekanbaru (4.0%), Medan (8.5%), and Batam (3.0%). The score of importance level of product quality is for effectivity (91.6%), ease of use (96.1%), flexibility (96.8%), technical specification (95.3%), durability (94.3%), and prestige (97.1%), while for customer service is tangibles (88.6%), reliability (87.0%), responsiveness (89.0%), assurance (94.6%), and empathy (96.8%). The results of explanatory research are product quality (R2 = 0.788; p = 0.003) and customer service (R2 = 0.820; p = 0.001) influence significantly on customer satisfaction, whereas customer satisfaction influence significantly on customer loyalty (R2 = 0.946; p = 0.000). Pest control operators as the applicator of pesticides for urban pest from PT Bayer Indonesia have satisfaction on product quality (95.2%) and customer service (90.5%).